Study on Stress Deformation of Pipe Shed in Shallow Buried Tunnel Considering Micro-Arch Effect - Yao Rong; Wanxu Du; Yang Sun; Fuyang Xiong; Lin Liu; Sufan Yu; Gang Jie (Advances in Civil Engineering)
This study aims to investigate the influence of the tiny soil arch effect generated by the soil between the steel tubes in the ring direction of the tunnel overrun tube shed on the force deformation of the steel tubes during the working period. By assuming the arch effect axis between the steel tubes is circular and intercepting any three adjacent steel tubes on the tunnel contour line to establish a vertical coordinate system, the equation of the arch axis and the coordinates of the arch top were derived. Referring to the calculation theory of the peripheral rock pressure of the Taishaki tunnel, the peripheral rock pressure borne by the steel tubes of the pipe shed under the consideration of the micro-arch effect was derived. Assuming the pipe shed acts as a semi-infinite long beam on Pasternak’s two-parameter elastic foundation, the pipe shed was divided into four sections axially based on the initial support application status and the tunneling position of the working surface. The controlling equations for each section were analyzed and solved. The theoretical deflection curves of the pipe shed were obtained using actual engineering construction parameters and were validated by monitoring the settlement values of the soil layer above the tunnel using multipoint displacement meters. The study shows that the initial support application status and the tunneling position of the working surface significantly affect the functioning mechanism of the pipe shed, causing it to play different roles at different stages. When the working surface advances to the target section, the pipe shed exerts a beam arch effect; when the working surface tunnels beyond the target section, the pipe shed exerts a combined beam effect. The deflection change trend of the pipe shed with the advancement of the working surface is characterized by rapidly increasing, rapidly decreasing, and slowly decreasing stages, with the maximum deflection change occurring above the working surface position. Considering the micro-arch effect, the theoretical deflection changes are larger and closer to the actual engineering situation compared to the existing theory that does not consider the micro-arch effect. The results provide theoretical references for the design and implementation of tunnel overrun pipe sheds, moving beyond mere engineering experience and validating new methods for monitoring the deformation of surrounding rock during tunnel construction, effectively ensuring construction safety during tunnel excavation.